PEMANFAATAN WEBSITE UNTUK MENDUKUNG KEGIATAN GEREJA JEMAAT GKPB PHILADELPHIA LEGIAN - I Made Dwi Ardiada; Gerson Feoh; Putu Wida Gunawan; Prastyadi Wibawa Rahayu; I Nyoman Bernadus; I Gede Pramana Ade Saputra; Agus Tommy Adi Prawira Kusuma (LPPM Institut Pendidikan Nusantara Global, 2026)
The development of information technology has brought significant changes in various aspects of life, including in the field of religious services. The church as a religious institution has a responsibility to convey information, coordinate activities, and establish effective communication with the congregation. The GKPB Philadelphia Legian Congregation Church has so far relied on conventional communication media such as bulletin boards and direct information delivery during services. This method has limitations in terms of reach and speed of information dissemination. Therefore, a digital media is needed that can facilitate the delivery of information, increase congregation participation, and support church service activities on an ongoing basis. Utilizing the church's official website as an information and communication center is one way to solve these problems. This community service activity is carried out through several stages including Needs Analysis, Website Design and Development, as well as Socialization and Training for church administrators on how to manage and update website content. Community service activities through the use of the website at the GKPB Philadelphia Legian Congregation Church can improve the effectiveness of church communication and services. This website is a strategic tool in supporting information dissemination and increasing congregation involvement.